Differences Post Delivery of Term Pregnancy Mean Maternal Serum Magnesium Level with Low Versus Normal Birth Weight - Dovy Djanas; Heri Farnas; Roza Sriyanti; Syntia Ambelina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Impaired fetal growth is still a major problem in obstetrics. Birth weight is usually used as an indicator of the well-being of the newborn and as an indirect measure of intrauterine nutrition during pregnancy and the mother's nutritional status during pregnancy. Magnesium contribute as a cofactor for various enzymes in the human body for metabolic processes. Fetal magnesium is obtained from maternal by transport through the placenta. In conditions of low magnesium levels will affect the epigenetic process, HPA-axis and GH-IGF axis of the fetus which in turn will result in fetal growth disorders. This study aims to determine the differences postdelivery serum magnesium levels of women at term pregnancy who give birth with low vs normal birth weight. Methods. This study used an observational analytic method with a cross sectional approach. Conducted from April 2020-December 2020 at Dr. M. Djamil Padang Central General Hospital and Network Hospital Faculty of Medicine, Andalas University. Total of 44 samples were divided into 2 groups, women who gave birth with low and normal birth weight babies. Samples was carried out at the Pramitha Padang Private Clinical Laboratory. Results: The mean maternal serum magnesium level in low birth weight group was 1.97 ± 0.16 mg/dL lower than normal birth weight group was 2.06 ± 0.14 mg/dL. Statistic test using the independent sample T test showed no differences in both groups (p = 0.064). Conclusion. The mean maternal serum magnesium level in low birth weight 1.97±0.16 mg/dL. The mean maternal serum magnesium level in normal birth weight was 2.06 ± 0.14 mg/dL. There was no significant difference on both groups.